What Does Equitable Co‐Production Entail? Three Perspectives - K. L. Akerlof; K. M. F. Timm; A. Chase; E. T. Cloyd; E. Heath; B. A. McGhghy; A. Bamzai‐Dodson; G. Bogard; S. Carter; J. Garron; M. Gavazzi; N. Kettle; et al. (Community Science, 2023)
Abstract Co‐production practices are increasingly being adopted in research conducted for the purpose of societal impact. However, the ways in which co‐production is conducted can perpetuate long‐standing inequity and inequality. This study investigates which principles of co‐production design are perceived to advance more equitable processes and outcomes based on the experiences of participants in three projects funded by U.S. federal programs that support decision‐relevant climate science, along with others engaged in co‐production efforts. We found three distinct perspectives: (a) Ways of Knowing and Power; (b) Participants and Interactions; and (c) Science as Capacity Building. Each viewpoint differentially weights the salience of statements associated with five dimensions of co‐production practices: (a) outcomes; (b) power; (c) place‐based, community rights and respect; (d) audiences and participation; and (e) interactions. In the final stage of the study, we hosted a workshop of participants representing various roles in co‐production efforts to vet and discuss each perspective. We found that the perspectives remained distinct after each of the groups selected core statements that reflect their views. The degree of variation across the three perspectives suggests that co‐production processes would benefit from an initial discussion of, and decisions about, rules of engagement to ensure that participants view the process as equitable.